Mechanisms and Consequences of Dopamine Depletion-Induced Attenuation of the Spinophilin/Neurofilament Medium Interaction. (28th May 2017) - Hiday, Andrew C.; Edler, Michael C.; Salek, Asma B.; Morris, Cameron W.; Thang, Morrent; Rentz, Tyler J.; Rose, Kristie L.; Jones, Lisa M.; Baucum, Anthony J.
Abstract : Signaling changes that occur in the striatum following the loss of dopamine neurons in the Parkinson disease (PD) are poorly understood. While increases in the activity of kinases and decreases in the activity of phosphatases have been observed, the specific consequences of these changes are less well understood. Phosphatases, such as protein phosphatase 1 (PP1), are highly promiscuous and obtain substrate selectivity via targeting proteins. Spinophilin is the major PP1-targeting protein enriched in the postsynaptic density of striatal dendritic spines. Spinophilin association with PP1 is increased concurrent with decreases in PP1 activity in an animal model of PD. Using proteomic-based approaches, we observed dopamine depletion-induced decreases in spinophilin binding to multiple protein classes in the striatum. Specifically, there was a decrease in the association of spinophilin with neurofilament medium (NF-M) in dopamine-depleted striatum. Using a heterologous cell line, we determined that spinophilin binding to NF-M required overexpression of the catalytic subunit of protein kinase A and was decreased by cyclin-dependent protein kinase 5. Functionally, we demonstrate that spinophilin can decrease NF-M phosphorylation. Our data determine mechanisms that regulate, and putative consequences of, pathological changes in the association of spinophilin with NF-M that are observed in animal models of PD.